Нострифікація дипломів про вищу освіту по спеціальності "Цивільна безпека", "Охорона праці" в Республіці Хорватії - Ільїнська, Ольга Ігорівна (Національний технічний університет "Харківський політехнічний інститут", 2023)
Визначено можливості та механізм визнання дипломів про вищу освіту (бакалавр, магістр) по спеціальності "Цивільна безпека" та "Охорона праці" в однієї з країн ЄС – Республиці Хорватії.

The possibilities and mechanism of recognition of higher education diplomas (bachelor's, master's) in the specialty "Civil Safety" and "Occupational Safety" in one of the EU countries - the Republic of Croatia - have been determined.
Nostrification of higher education diplomas in the specialty "Civil security", "Occupational safety" in the Republic of Croatia
Keywords: визнання дипломів; нострифікація дипломів; спеціальність цивільна безпека; охорона праці; recognition of diplomas; nostrification of diplomas; civil safety specialty; Labor protection